Analysis of Halal Tourism Development Potential In Pandeglang Regency, Banten Province, Indonesia - Hani Muflihah; Malika Hajji; Deden Inayatullah (Ecopreneur : Journal of Sharia Economics Study Program, 2024)
Tourism plays a major role in boosting the global economy by educating about the nature, culture and diversity of a region. Halal tourism, which conforms to Islamic principles, provides Muslim-friendly facilities. Pandeglang Regency has great potential to become the centre of halal tourism in Banten as the majority of the population is Muslim. However, its development has not been optimal due to lack of infrastructure, government support, and community readiness. This study aims to evaluate the potential, obstacles, and solutions of halal tourism development in Pandeglang with qualitative methods through interviews, observations, and documentation. The objectives in this study are (1) to find out how the potential of halal tourism development in Pandeglang district, (2) to find out what are the obstacles to the potential of halal tourism development in Pandeglang district and (3) to find out how the solution of halal tourism development in Pandeglang district. The method used in this research is a qualitative approach that describes and discusses the state of the object under study based on existing facts. The data used in this research is primary data using interviews, observation, and documentation. Furthermore, it was analysed using the analysis method of data reduction, data presentation, and drawing conclusions. The results of this study are the development of halal tourism in Pandeglang regency has begun to be carried out slowly, even though the development of halal tourism in Pandeglang regency has been carried out slowly.